Insights into the mechanism of inhibition of tryptophan 2, 3-dioxygenase by isatin derivatives. (1st November 2016) - Pantouris, Georgios; Loudon-Griffiths, James; Mowat, Christopher G.
Abstract: Tryptophan 2, 3-dioxygenase (TDO) is a cytosolic protein with a proven immunomodulatory function that promotes tumoral immune resistance and proliferation. Despite the interest in TDO as a therapeutic target in cancer treatment, the number of biologically useful inhibitors is limited. Herein, we report isatin derivatives as a new class of TDO inhibitors. Through structure–activity relationships and molecular docking studies, we optimized the inhibition potency of isatin derivatives by >130-fold and elucidated the mechanistic details that control their mode of action. Hydrogen bond interactions between the compound and key active site residues of TDO, freedom upon rotation of the C3 chemical moiety and the presence of chlorines in the benzene ring of the compound comprise the properties that an isatin-based inhibitor requires to effectively inhibit the enzymatic activity of TDO.